Nephtyidae (Annelida: Phyllodocida) of Lizard Island, Great Barrier Reef, Australia - Murray, Anna; Wong, Eunice; Hutchings, Pat (Zootaxa, 2015)
Seven species of the family Nephtyidae are recorded from Lizard Island, none previously reported from the Great Barrier Reef. Two species of Aglaophamus, four species of Micronephthys, one new and one previously unreported from Australia, and one species of Nephtys, were identified from samples collected during the Lizard Island Polychaete Workshop 2013, as well as from ecological studies undertaken during the 1970s and deposited in the Australian Museum marine invertebrate Collections. A dichotomous key to aid identification of these species newly reported from Lizard Island is provided.